A novel multisystem disease associated with recessive mutations in the tyrosyl‐tRNA synthetase (YARS) gene. Issue 1 (15th September 2016) - Nowaczyk, Małgorzata J. M.; Huang, Lijia; Tarnopolsky, Mark; Schwartzentruber, Jeremy; Majewski, Jacek; Bulman, Dennis E.; ,; Hartley, Taila; Boycott, Kym M.
Abstract : Aminoacyl‐tRNA synthetases (ARSs) are a group of ubiquitously expressed enzymes that are best known for their function in the first step of protein translation but have been increasingly associated with secondary functions including transcription and translation control and extracellular signaling. Mutations in numerous ARSs have been linked to a growing number of both autosomal dominant and autosomal recessive human diseases. The tyrosyl‐tRNA synthetase (YARS) links the amino acid tyrosine to its cognate tRNA. We report two siblings who presented with failure to thrive (FTT), hypertriglyceridemia, developmental delay, liver dysfunction, lung cysts, and abnormal subcortical white matter. Using exome sequencing the siblings were found to harbor bi‐allelic pathogenic‐appearing variants within the YARS gene (NM_003680.3):c.638C>T p.(Pro213Leu) and c.1573G>A p.(Gly525Arg). These YARS variants occur in the catalytic domain and the C‐terminal domain, respectively. Mutations in YARS have been previously associated with an autosomal dominant form of Charcot‐Marie‐Tooth (CMT); our findings suggest the disease spectrum associated with YARS dysregulation is broader than peripheral neuropathy. © 2016 Wiley Periodicals, Inc.